Design and Construction of Underground Cable Fault Location and Notification System. - Mugisha, Simon (Kabale University, 2023)
The overhead lines are mostly used when compared to underground cables though in towns and cities, underground cables are preferred. The underground cables are largely used in urban areas instead of overhead lines. This is because they have minimized transmission losses, can lead to death of human beings and destruction of property like buildings. This comes as a result of tall buildings being near the conductors. In determining the location of a fault point in the underground cable, the AC power in the cables is first switched off because they cannot carry both AC power and DC power at once and the standard concept of Ohms law is applied that is, when a low DC voltage is applied at the feeder end through a series resistors representing the cable lines, then current would vary depending upon the location of the fault point in the cable. In case there is a short circuit (Line to Ground), the voltage across series resistors changes depending on the fault location. This voltage is then fed to an Analogue to Digital Converter (ADC) to develop precise digital signal and the Arduino nano communicates the LCD screen to display the status of the underground cables by showing the fault location (distance) in kilometers with its respective phase.